2021
DOI: 10.1186/s12870-021-02830-z
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid signaling pathway in Capsicum chinense suspension cells as a key response to consortium infection

Abstract: Background Mexico is considered the diversification center for chili species, but these crops are susceptible to infection by pathogens such as Colletotrichum spp., which causes anthracnose disease and postharvest decay in general. Studies have been carried out with isolated strains of Colletotrichum in Capsicum plants; however, under growing conditions, microorganisms generally interact with others, resulting in an increase or decrease of their ability to infect the roots of C. chinense seedli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…These roles include reducing phosphatidic acid (PA) levels (by almost 30%), PLC inhibition [ 34 ], and rapid activation of PLC transcription in mere minutes [ 35 ], all of which are responses to aluminum stress. Additionally, high levels of diacylglycerol pyrophosphate (DGPP) and PA were found in response to consortium infection involving PLC/DGK pathways [ 36 ]. This evidence establishes that PLDs produce another PA pool in response to different stresses.…”
Section: Introductionmentioning
confidence: 99%
“…These roles include reducing phosphatidic acid (PA) levels (by almost 30%), PLC inhibition [ 34 ], and rapid activation of PLC transcription in mere minutes [ 35 ], all of which are responses to aluminum stress. Additionally, high levels of diacylglycerol pyrophosphate (DGPP) and PA were found in response to consortium infection involving PLC/DGK pathways [ 36 ]. This evidence establishes that PLDs produce another PA pool in response to different stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Anggrahini et al (2022) reported that Colletotrichum, the causal agent of chili anthracnose in C. annum and C. frutescens, is isolated from symptomatic chili fruit and leaves at altitudes ranging from 5 to 343 m above sea level. Furthermore, accordingAlmeida et al (2017) andSánchez- Sandoval et al (2021), anthracnose disease is detected in Capsicum chinense in Brazil and México.…”
mentioning
confidence: 99%